2016
DOI: 10.1007/s00062-016-0500-9
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Dedicated Surface Coil in Dental MRI Provides Superior Image Quality in Comparison with a Standard Coil

Abstract: Dental MRI benefits profoundly from using a dedicated dental coil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
10

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 14 publications
0
7
0
10
Order By: Relevance
“…More recent studies showed an accurate and high‐resolution display of the inferior alveolar nerve and intraoral anatomy within clinically feasible scanning times using specific surface coils and the interference of dental implants and inferior alveolar nerve using MRI (Flügge et al, 2016; Gradl et al, 2017; Kreutner et al, 2017; Wanner et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies showed an accurate and high‐resolution display of the inferior alveolar nerve and intraoral anatomy within clinically feasible scanning times using specific surface coils and the interference of dental implants and inferior alveolar nerve using MRI (Flügge et al, 2016; Gradl et al, 2017; Kreutner et al, 2017; Wanner et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we did not use any dedicated surface coils as described in earlier studies 32 because a good signal‐to‐noise ratio and a short acquisition time could be achieved without any additional coils. This is mainly due to the good gradient hardware performance of the employed 3 T scanner (Elition, Philips Healthcare) used and the acquisition time reduction made possible by the combination of compressed sensing with sensitivity encoding (SENSE) parallel imaging 33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…Na rotina clínica, exames de RM feitos para investigar estruturas odontológicas são geralmente realizados com bobinas de cabeça e pescoço, o que diminui a intensidade do sinal de pequenas estruturas. Entretanto, alguns trabalhos demonstraram o uso e construção de bobinas específicas para melhorar a qualidade das imagens de RM para o uso na odontologia [45][46][47]58]. Como exemplo, no estudo de Gradl et al, os autores avaliaram e compararam o uso de uma bobina de superfície que cobre toda a dentição em relação à bobina padrão utilizada de cabeça e pescoço.…”
Section: Methodsunclassified
“…Como exemplo, no estudo de Gradl et al, os autores avaliaram e compararam o uso de uma bobina de superfície que cobre toda a dentição em relação à bobina padrão utilizada de cabeça e pescoço. Uma relação de sinal-ruído 3,5 vezes maior foi obtida utilizando a bobina "dentária" [47]. Considerando que esta bobina de superfície permite a obtenção de imagens de estruturas anatômicas mais superficiais, são sugeridos estudos futuros nos quais bobinas intraorais para a avaliação de osso alveolar sejam construídas e sequências de pulso específicas para avaliação do tecido adiposo em medula óssea amarela presente em osso alveolar, como as que foram estudadas neste estudo, sejam utilizadas de forma concomitante.…”
Section: Methodsunclassified
See 1 more Smart Citation